Light glazed ceramic large brick and preparation method thereof
By using low-temperature fast firing technology and adjusting the composition of the ceramic layer during the firing process of large ceramic tiles, the problems of large stress and increased convex deformation in the glaze layer during the firing process of large ceramic tiles are solved, and the hardness, wear resistance and earthquake resistance of large ceramic tiles are significantly improved.
Patent Information
- Application Number
- CN202510024388.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-14
AI Technical Summary
During the firing process of existing glazed ceramic tiles, the expansion coefficient of the glaze layer is smaller than that of the ceramic tile, resulting in large stress in the glaze layer, increasing convex deformation during firing, making it difficult to control the stability of product quality.
The low-temperature fast firing technology is adopted to control the shape of the ceramic tile to be difficult to change during the firing process. By adjusting the composition of the embryo body layer, the base glaze layer and the surface glaze layer, the hardness and wear resistance of large ceramic tiles are improved.
It improves the hardness and wear resistance of ceramic large bricks, with wear quality of 0.08~0.11g/12000 rpm, Vickers hardness is between 746.8~768.2, and the flexural strength can reach 50~63MPa. It has stable performance and is not easy to break, which increases the aesthetics of use and shock resistance.
Smart Images

Figure BDA0005232324220000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to a large lightweight glazed ceramic brick and a preparation method thereof. Background Art
[0002] Among many decorative materials, ceramic tiles can meet people's requirements for visual effects, beautiful design and service life, and are widely used in the field of architectural decoration. Among them, glazed ceramic tiles are novel in design, high in gloss, flat and have high wear resistance. They combine the excellent properties of polished tiles, antique tiles and porcelain tiles, and are widely used for paving interior walls and floors of houses that have high requirements for the decorative performance and stain resistance of ceramic tiles.
[0003] At present, the preparation steps of lightweight glazed ceramics are mainly divided into: ball milling of raw materials, screening, spray drying and powdering, pressing and molding of blanks, applying base glaze, glaze decoration, applying full glaze, firing, polishing and finally obtaining finished products. The glazed tiles have excellent characteristics such as low water absorption, high flexural strength, good acid and alkali corrosion resistance, wear resistance, and transparent and bright appearance. However, the expansion coefficient of the glaze layer of the current glazed products is smaller than that of the ceramic tile body, and the glaze layer is subjected to greater internal stress. After the glaze layer is thickened, the convex deformation of the ceramic tile increases during firing, which is not easy to control in production and it is difficult to ensure the stability of product quality. Summary of the invention
[0004] In view of the problems existing in the background technology, the present invention provides a lightweight glazed ceramic large brick and a preparation method thereof, which adopts low-temperature fast firing technology, and the shape of the ceramic tile is not easy to change during the firing process. The fired ceramic large brick has a certain anti-pollution property. More importantly, the hardness and wear resistance are greatly improved, and it is not easy to break, which increases the aesthetics of the ceramic large brick. It is achieved through the following technical solutions:
[0005] The lightweight glazed ceramic large tile is composed of a body layer, a bottom glaze layer, and a surface glaze layer;
[0006] The embryo layer is composed of the following components by weight: 35-42 parts of kaolin, 25-30 parts of clay, 8-12 parts of cordierite, 10-15 parts of quartz, 5-9 parts of alumina, 4-9 parts of potassium feldspar, and 1-3 parts of a binder;
[0007] The bottom glaze layer is composed of the following components by weight: 25-37 parts of potassium feldspar, 15-20 parts of burnt talc, 15-20 parts of frit, 10-25 parts of quartz, 8-10 parts of calcite, 5-10 parts of zirconium silicate, and 5-8 parts of burnt zinc oxide;
[0008] The surface polishing glaze is composed of the following components by weight: 30-40 parts of frit, 20-30 parts of clay, 15-22 parts of albite, 10-15 parts of zinc oxide, 10-15 parts of stone powder and 8-13 parts of kaolin.
[0009] Preferably, the binder is selected from polyvinyl alcohol, phenolic resin, and wax emulsion.
[0010] A method for preparing a large lightweight glazed ceramic tile comprises the following steps:
[0011] Step (a): firstly, the embryo raw material is coarsely crushed by a jaw crusher, and then the crushed raw material and the binder are added to a ball mill according to the number of parts for wet ball milling;
[0012] Step (b): the slurry is screened and iron removed before spray granulation. The spray-dried particles are transported from the bottom of the drying tower to a powder bin via a belt and stored for 20 to 24 hours to homogenize the moisture.
[0013] Step (c): the homogenized powder is spread in the mold of the press by a distributor according to the production process, and the press is pressed to form a blank;
[0014] Step (d): drying the embryo;
[0015] Step (e): applying a layer of white base glaze on the surface of the embryo and drying at 120° C. for 12 hours;
[0016] Step (f): inkjet printing is then performed to carry out pattern decoration, and after drying at room temperature for 30 minutes, a layer of polishing glaze is added on the surface of the glaze layer to protect the pattern;
[0017] Step (g): The green bricks are fired by low-temperature fast firing technology, and then edged, polished, sorted and packaged and stored in a warehouse.
[0018] Preferably, the ball milling conditions in step (a) are ball: material: water = 2: 1: 0.5, and the ball milling time is 0.5 to 1 hour.
[0019] Preferably, the slurry in step (b) is sieved through a 200-mesh screen.
[0020] Preferably, the drying conditions for the green embryo in step (d) are to use a 3-5 layer roller kiln, set the drying temperature to 180-200° C., and the drying time to 1.5-2 hours.
[0021] Preferably, the specific gravity of the white base glaze is 1.74-1.78 g / cm 3 , glaze application amount is 420~540g / m 2 ; The specific gravity of the polished glaze is 1.82~1.88g / cm 3 , glaze application amount is 520~620g / m 2 .
[0022] Preferably, the low temperature fast calcination technology in step (g) is divided into three calcination stages:
[0023] The first stage is calcined in nitrogen at a rate of 10-15°C / min from room temperature to 300-360°C for 0.5-1.5 hours;
[0024] The second stage is calcined in nitrogen at a rate of 15-20°C / min from 300-360°C to 700-800°C for 2-3 hours;
[0025] The third stage is calcined in nitrogen at a rate of 10-15°C / min from 700-800°C to 950-1050°C for 0.5-1 hour.
[0026] Compared with the existing technology, the above technical solution of the present invention has the following beneficial effects:
[0027] The present invention adopts low-temperature fast-firing technology to improve the sintering performance of ceramics, and improve the strength and hardness of ceramics. Its wear quality is 0.08-0.11g / 12000 revolutions, Vickers hardness (HV0.5) is between 746.8-768.2, and its flexural strength can reach 50-63MPa. It has stable performance, is safe and firm, and is not easy to break when subjected to a certain pressure or impact force. At the same time, the ceramic bricks obtained by the present invention have a certain degree of shock resistance, can adapt well to sudden temperature changes, and are not easy to be damaged. These properties show that the lightweight glazed ceramic bricks described in the present invention have multiple uses such as wall and floor decoration of building spaces. DETAILED DESCRIPTION
[0028] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0029] It should be noted that the experimental methods used in the implementation examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0030] In the present invention, unless otherwise specified, all "parts" and percentages (%) refer to percentages by weight.
[0031] In the present invention, unless otherwise specified, the sum of all percentages in all compositions is 100%.
[0032] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a-b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0033] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0034] In the present invention, unless otherwise specified, all the steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially; for example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially; for example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0035] In the present invention, unless otherwise specified, the specific numerical values and specific substances in the embodiments of the present invention may be combined with other features of the description part of the present invention; for example, if the specification mentions that the reaction temperature is 10-100°C, and the embodiment mentions that the reaction temperature is 20°C, then it can be considered that the present invention has specifically disclosed the range of 10-20°C, or the range of 20-100°C, and this range can be combined with other features of the description part to form a new technical solution.
[0036] Example 1
[0037] (1) First, 35 parts of kaolin, 28 parts of clay, 9 parts of cordierite, 13 parts of quartz, 8 parts of alumina, and 5 parts of potassium feldspar were coarsely crushed by a jaw crusher, and then the crushed raw materials and 2 parts of polyvinyl alcohol were added to a ball mill at a ratio of ball: material: water = 2:1:0.5 for wet ball milling, and the ball milling time was 0.5 hours;
[0038] (2) The slurry after ball milling is passed through a 200-mesh sieve to remove the iron in the slurry and then spray granulation is performed. The spray-dried particles are transported from the bottom of the drying tower by a belt into a powder bin and stored for 20 hours to homogenize the moisture;
[0039] (3) The homogenized powder is spread in the mold of the press by a distributor according to the production process, and the press is pressed to form a blank;
[0040] (4) Drying the green embryo in a 3-5 layer roller kiln at 200° C. for 1.5 hours;
[0041] (5) applying a layer of white base glaze consisting of 30 parts of potassium feldspar, 20 parts of calcined talc, 15 parts of frit, 10 parts of quartz, 10 parts of calcite, 9 parts of zirconium silicate, and 6 parts of calcined zinc oxide on the surface of the body and drying at 120° C. for 12 hours;
[0042] (6) Then, inkjet printing is performed to decorate the pattern. After drying at room temperature for 30 minutes, a layer of glaze consisting of 37 parts of frit, 20 parts of clay, 15 parts of albite, 10 parts of zinc oxide, 10 parts of stone powder, and 8 parts of kaolin is added on the surface of the glaze layer to protect the pattern.
[0043] (7) The temperature of the green bricks is raised from room temperature to 300°C at a rate of 10-15°C / min and calcined in nitrogen for 0.5-1.5 hours; the second stage is raised from 300°C to 700°C at a rate of 15-20°C / min and calcined in nitrogen for 2-3 hours; the third stage is raised from 700°C to 950°C at a rate of 10-15°C / min and calcined in nitrogen for 0.5-1 hour; finally, the finished products are stored in a warehouse after edge grinding, polishing, sorting and packaging.
[0044] Example 2
[0045] (1) First, 40 parts of kaolin, 25 parts of clay, 8 parts of cordierite, 12 parts of quartz, 6 parts of alumina, and 6 parts of potassium feldspar were coarsely crushed by a jaw crusher, and then the crushed raw materials and 3 parts of polyvinyl alcohol were added to a ball mill at a ratio of ball: material: water = 2:1:0.5 for wet ball milling, and the ball milling time was 0.5 hours;
[0046] (2) The ball-milled slurry is passed through a 200-mesh sieve to remove the iron in the slurry and then spray granulated. The spray-dried particles are transported from the bottom of the drying tower to a powder bin via a belt and stored for 20 hours to homogenize the moisture;
[0047] (3) The homogenized powder is spread in the mold of the press by a distributor according to the production process, and the press is pressed to form a blank;
[0048] (4) Drying the green embryo in a 3-5 layer roller kiln at 180° C. for 2 hours;
[0049] (5) applying a layer of white base glaze consisting of 33 parts of potassium feldspar, 18 parts of calcined talc, 15 parts of frit, 16 parts of quartz, 8 parts of calcite, 5 parts of zirconium silicate, and 5 parts of calcined zinc oxide on the surface of the body and drying at 120° C. for 12 hours;
[0050] (6) Then, inkjet printing is performed to decorate the pattern. After drying at room temperature for 30 minutes, a layer of glaze consisting of 36 parts of frit, 21 parts of clay, 15 parts of albite, 10 parts of zinc oxide, 10 parts of stone powder, and 8 parts of kaolin is added on the surface of the glaze layer to protect the pattern.
[0051] (7) The green bricks are calcined in nitrogen at a rate of 10-15°C / min from room temperature to 360°C for 1.5 hours; the second stage is calcined in nitrogen at a rate of 15-20°C / min from 360°C to 800°C for 2-3 hours; the third stage is calcined in nitrogen at a rate of 10-15°C / min from 800°C to 1050°C for 0.5-1 hour, and finally edge grinding, polishing, sorting and packaging are put into warehouse for storage.
[0052] Example 3
[0053] The difference between Example 3 and Example 1 is that the binder of Example 3 adopts phenolic resin.
[0054] The other raw materials and preparation method of the lightweight glazed ceramic large brick in Example 3 are the same as those in Example 1.
[0055] Example 4
[0056] The difference between Example 4 and Example 1 is that the composition of the embryo layer is different. The embryo composition of Example 4 is 38 parts of kaolin, 26 parts of clay, 10 parts of cordierite, 10 parts of quartz, 9 parts of alumina, 6 parts of potassium feldspar, and 1 part of polyvinyl alcohol. Other preparation raw materials and preparation methods are the same as those in Example 1.
[0057] Comparative Example 1
[0058] The difference between Comparative Example 1 and Experimental Example 1 is that the green bricks are calcined continuously at 1250° C. for 3 hours, and the components, addition amounts and preparation methods of other raw materials are the same as those in Example 1.
[0059] Performance Testing
[0060] The wear resistance, hardness and flexural strength of the lightweight glazed ceramic tiles produced in Examples 1 to 4 and Comparative Example 1 were tested, wherein the wear resistance index was measured according to the standard "GB / T3810.7-2016 / ISO10545-7:1996" and expressed as wear mass, the hardness was measured according to the method in GB / T 4340.1-2009 "Metallic Materials Part 1: Test Method Vickers Hardness Test", and the flexural strength was tested according to "GB / T3810.4-2016 Ceramic Tile Test Method". The results are shown in Table 1.
[0061] Table 1
[0062]
[0063] As shown in Table 1, the ceramic bricks prepared by the method of the present invention have excellent wear resistance and a certain hardness and are not easy to break. The mechanical properties of the comparative example 1 without staged low-temperature calcination are greatly reduced and cannot meet the actual application requirements.
[0064] Seismic test
[0065] The products obtained in Examples 1 to 4 were subjected to a shock resistance test, and no bursting or cracking occurred after 20 thermal shock resistance tests.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A lightweight glazed ceramic large brick, characterized in that: It is composed of embryo layer, bottom glaze layer and surface polishing glaze layer; The embryo layer is composed of the following components by weight: 35-42 parts of kaolin, 25-30 parts of clay, 8-12 parts of cordierite, 10-15 parts of quartz, 5-9 parts of alumina, 4-9 parts of potassium feldspar, and 1-3 parts of a binder; The bottom glaze layer is composed of the following components by weight: 25-37 parts of potassium feldspar, 15-20 parts of burnt talc, 15-20 parts of frit, 10-25 parts of quartz, 8-10 parts of calcite, 5-10 parts of zirconium silicate, and 5-8 parts of burnt zinc oxide; The surface polishing glaze is composed of the following components by weight: 30-40 parts of frit, 20-30 parts of clay, 15-22 parts of albite, 10-15 parts of zinc oxide, 10-15 parts of stone powder and 8-13 parts of kaolin.
2. A large lightweight glazed ceramic tile according to claim 1, characterized in that: The binder is selected from polyvinyl alcohol, phenolic resin and wax emulsion.
3. A method for preparing a lightweight glazed ceramic large brick, characterized in that: The preparation method comprises the following steps: Step (a): firstly, the embryo raw material is coarsely crushed by a jaw crusher, and then the crushed raw material and the binder are added to a ball mill according to the number of parts for wet ball milling; Step (b): the slurry is screened and iron removed before spray granulation. The spray-dried particles are transported from the bottom of the drying tower to a powder bin via a belt and stored for 20 to 24 hours to homogenize the moisture. Step (c): the homogenized powder is spread in the mold of the press by a distributor according to the production process, and the press is pressed to form a blank; Step (d): drying the embryo; Step (e): applying a layer of white base glaze on the surface of the embryo and drying at 120° C. for 12 hours; Step (f): inkjet printing is then performed to carry out pattern decoration, and after drying at room temperature for 30 minutes, a layer of glaze is added on the surface of the glaze layer to protect the pattern; Step (g): The green bricks are fired by low-temperature fast firing technology, and then edged, polished, sorted and packaged and stored in a warehouse.
4. The method for preparing a light glaze-polished ceramic large tile according to claim 3, characterized in that: The ball milling conditions in step (a) are ball: material: water = 2: 1: 0.5, and the ball milling time is 0.5 to 1 hour.
5. The method for preparing a large lightweight glazed ceramic tile according to claim 3, characterized in that: Step (b) The slurry is passed through a 200-mesh sieve.
6. The method for preparing a large lightweight glazed ceramic tile according to claim 3, characterized in that: In step (d), the drying conditions for the green embryo are to use a 3-5 layer roller kiln, set the drying temperature to 180-200° C., and the drying time to 1.5-2 hours.
7. The method for preparing a large lightweight glazed ceramic tile according to claim 3, characterized in that: The specific gravity of white base glaze is 1.74~1.78g / cm 3 , glaze application amount is 420~540g / m 2 ; The specific gravity of the polished glaze is 1.82~1.88g / cm 3 , glaze application amount is 520~620g / m 2 .
8. The method for preparing a large lightweight glazed ceramic tile according to claim 3, characterized in that: The low temperature fast calcination technology in step (g) is divided into three calcination stages: The first stage is calcined in nitrogen at a rate of 10-15°C / min from room temperature to 300-360°C for 0.5-1.5 hours; The second stage is calcined in nitrogen at a rate of 15-20°C / min from 300-360°C to 700-800°C for 2-3 hours; The third stage is calcined in nitrogen at a rate of 10-15°C / min from 700-800°C to 950-1050°C for 0.5-1 hour.
9. A lightweight glazed ceramic large brick is obtained by the preparation method according to any one of claims 3 to 8.
Citation Information
Cited By
Ceramic glaze-finished tile directly fired based on concentrated solar energy and preparation method thereof
CN122831731A